Das Bild der Frau in der Plastik des 20. Jahrhunderts. - Wilhelm-Lehmbruck-Museum, Duisburg (Duisburg : Wilhelm-Lehmbruck-Museum, 1986)
Ahearn, John ; Archipenko, Alexander ; Barlach, Ernst ; Baroni, Claudio ; Beuys, Joseph ; de Boer, Saskia ; Butler, Reginald ; Gaudier-Brzeska, Henry ; Giacometti, Alberto ; Gonzàlez, Julio ; Hanson, Duane ; Hiller, Anton ; Höckelmann, Antonius ; Kasper, Ludwig ; Kienholz, Edward ; Kollwitz, Käthe ; Lehmbruck, Wilhelm ; etc.
Das Bild der Frau in der Plastik des 20. Jahrhunderts, Wilhelm-Lehmbruck-Museum, Duisburg, 4. Mai bis 15. Juni 1986
boek